Cumulative semantic inhibition in Spanish verb production - Sevilla, Yamila Alejandra (2020)
This paper reports an experiment designed to assess the occurrence of lexical interference in verb production in Spanish. Using the semantic competitors paradigm (Howard et al., 2006), we show that the higher the number of verbs of the same category produced, the longer it takes to retrieve another verb of the same category in a picture naming task. According to our data, the production of a related verb delays the naming of a new member of the category by 20 ms., which means that, as is the case with nouns, semantically related verbs compete for selection. These results support the statement that, regardless their differences with respect to semantic representation and organization, verb and noun selection are guided by the same principles. Methodologically, our findings confirm that the paradigm is highly sensitive to semantic proximity effects, in terms of either categories or features. In light of these findings, we discuss the reasons why previous studies exploring semantic relatedness effects in verb production, most of them using the picture-word interference paradigm, have led to inconclusive and sometimes contradictory results.